Inovasi Pembelajaran Berbasis Game untuk Menarik Minat Generasi Z dan Alpha - Ari Dewantara; Defqiyani Fauza; Rayi Darma Reksa (Progressive Journal of Educational Science, 2025)
The development of digital technology has brought significant changes to the characteristics of students, especially Generation Z and Generation Alpha who have grown up as digital natives. This condition demands learning innovations that are able to accommodate their learning needs, which tend to be interactive, visual, and experience-based. This article aims to examine the learning characteristics of Generation Z and Generation Alpha, the concepts and principles of Game-Based Learning, its benefits in increasing learning interest and motivation, implementation strategies, and digital tools that support game-based learning. This research uses a qualitative approach with a literature study method, through the analysis of various literature sources in the form of reputable journal articles, academic books, and relevant scientific publications. The results of the study show that Game-Based Learning is a relevant and effective learning approach to increase the engagement, motivation, and conceptual understanding of digital generation students. In addition, the application of this method also contributes to the development of students' social and emotional skills. With proper planning, digital support, and teacher competence in designing game-based learning, Game-Based Learning has the potential to be an innovative solution in improving the quality of learning in the digital era.